2008
DOI: 10.1016/j.neuroscience.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Timing in the absence of supraspinal input I: Variable, but not fixed, spaced stimulation of the sciatic nerve undermines spinally-mediated instrumental learning

Abstract: Rats with complete spinal transections are capable of acquiring a simple instrumentally trained response. If rats receive shock to one hindlimb when the limb is extended (controllable shock), the spinal cord will learn to hold the leg in a flexed position that minimizes shock exposure. If shock is delivered irrespective of leg position, subjects do not exhibit an increase in flexion duration and subsequently fail to learn when tested with controllable shock (learning deficit). Just 6 min of variable intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 87 publications
5
77
0
Order By: Relevance
“…For subjects in the fixed spaced condition, shocks occurred at regular (2-s) intervals. Variable stimulation was created using a rectangular distribution that varied between 0.2 and 3.8 s, with a mean interstimulus interval (ISI) of 2 s. Prior work has shown that variable shock undermines learning (Crown et al, 2002; Baumbauer et al, 2007; Baumbauer et al, 2008; Ferguson et al, 2008; Baumbauer et al, 2009), while fixed shock does not (Baumbauer et al, 2008; Baumbauer et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For subjects in the fixed spaced condition, shocks occurred at regular (2-s) intervals. Variable stimulation was created using a rectangular distribution that varied between 0.2 and 3.8 s, with a mean interstimulus interval (ISI) of 2 s. Prior work has shown that variable shock undermines learning (Crown et al, 2002; Baumbauer et al, 2007; Baumbauer et al, 2008; Ferguson et al, 2008; Baumbauer et al, 2009), while fixed shock does not (Baumbauer et al, 2008; Baumbauer et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…peripheral capsaicin or carrageenan) impair this learning (Ferguson et al, 2006; Hook et al, 2008). Interestingly, variable intermittent shock at an intensity that activates C-fibers also impairs instrumental learning and this effect lasts at least 24 hr (Crown et al, 2002; Baumbauer et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to uncover a pharmacological target for stimulus-dependent maladaptive plasticity in SCI, our team recently tested the impact of below-level nociceptive stimulation on ventral spinal motor neurons after SCI, using the same uncontrollable C-fiber-strength electronociceptive stimulation paradigm extensively described by Grau and colleagues. 82,[115][116][117][118] Our hypothesis was that aberrant stimulation would generate intrinsic ventral horn motorneuron changes after SCI similar to those known to be involved in maladaptive sensory plasticity in the dorsal horn in pain syndromes. Pain plasticity has been shown to be mediated by rapid alterations in synaptic AMPA receptor (AM-PAR) levels and phosphorylation similar to those observed in brain-dependent learning and memory.…”
Section: Nociceptive/noxious Afferent Inputmentioning
confidence: 99%
“…Specific cellular mechanisms involved in the maladaptive plasticity as determined by Grau et al, are dependent on post-synaptic activation of group I metabotropic glutamate receptor (mGluR) as well as substance P receptor neurokinin 1 (NK1R) which leads to an increased intracellular calcium, activation of protein kinase C (PKC), CamKII and phosphoinositide 3-kinase (PI3K) [293][294][295]. It is proposed that the activity of calcium-dependent kinases leads to an altered NMDA and AMPA receptor function [296,297].…”
Section: Nociceptive Afferents Modulate Locomotor Cpgmentioning
confidence: 99%